Flexibility in educational systems - concept, indicators, and directions for future research - Weßling, Katarina [Verfasser]; Van der Velden, Rolf K. W. [Verfasser] (Universität Maastricht, 2021)
„This conceptual contribution discusses the idea of flexibility of educational systems from a multidisciplinary perspective. We define flexibility as possibilities that are provided by an education system to modify standard (predetermined) learning paths, which result from the structured organization of education. Flexibility at the macro level (i.e., educational system) can relate to policies such as the mobility between educational tracks within stratified systems. At the meso level (i.e., school, classroom), flexibility can entail practices of differentiated instruction. We believe that a systematic integration of flexibility in educational research can provide new insights on individuals’ educational outcomes. Implicitly and unconnectedly, the idea of flexibility exists in several strands of research, typically focusing on educational-system effects on individual outcomes such as (1) sociological research on structural features of the education system, (2) psychological literature on educational effectiveness, and (3) economic research drawing on the education production function. We bridge these three fundamental strands of research with the aim to exemplify the concept of flexibility. In doing so, we propose a definition of flexibility, outline dimensions as well as corresponding indicators. To conclude, we provide some directions for future research.“ (authors‘ abstract; BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; 370; Bildungsforschung; Bildungssystem; Flexibilität; Definition; Flexibilitätsforschung